State Responses to the Tax Cuts and Jobs Act: An Analysis from Indiana and Missouri - Richard C. Byrd; Stephen J. Madden; Jeffrey M. Raney; John T.M. Whiteman (Washington University Journal of Law & Policy, 2019)
This Article, authored by lawyers from the Indiana Department of Revenue and Missouri Department of Revenue, is intended to address, and hopefully add clarity to, the complexities of state taxation under the Tax Cuts and Jobs Act of 2017 (“TCJA”). After a brief historical and general overview of the TCJA, this Article focuses on seven distinct topics within the TCJA from a state perspective. These topics are: (1) Business Assets Expensing; (2) the TCJA’s treatment of 529 Accounts; (3) the 30% Business Interest Limitation; (4) the Transition Tax (also referred to as “Deemed Repatriation”); (5) GILTI, or Global Intangible Low-Taxed Income; (6) the elimination of the Personal and Dependency Exemption Deductions; and (7) the Qualified Business Income Deduction. For each topic, this Article gives an overview of the associated TCJA provisions, addresses some responses of the states to these provisions, and provides opportunity for discussion of possible or actual responses by Indiana and/or Missouri.
Keywords: Tax law; Taxation; Tax Cuts and Jobs Act; TCJA